Use of low-intensity laser therapy for treatment and prevention of oral mucositis lesions in a leukemic patient: Case report (Research, Society and Development, 2024)
Leukemias are malignant hematologic neoplastic diseases that result from the uncontrolled growth of clonal cells in the bone marrow. The treatment of leukemias has important side effects, among them, oral mucositis (OM), the most common complication in the oral cavity, presenting inflammation of the mucosa, erythema and painful ulcers. A therapy already widely disseminated in the literature due to its numerous positive results in the treatment of OM, is low-intensity laser therapy (LLLT), which has beneficial effects on the irradiated tissues. The present study aims to report a clinical case where LLLT was used for the treatment and prevention of OM lesions in a patient with acute promyelocytic leukemia. Patient M.S.S, 40 years old, presented intense dryness of the oral mucosa at the beginning of chemotherapy, so an opinion was requested for evaluation by the Hospital Dentistry team. During clinical examination, multiple ulcerated lesions were observed in the oral mucosa. Therefore, the approach adopted was to use Flogoral spray, artificial saliva and initiate the laser therapy protocol for the management of OM. LLI demonstrated significant results, with clinical improvement, pain minimization and tissue regeneration. The patient continued to be monitored in the remaining chemotherapy cycles for the laser therapy protocol to prevent OM. OM is a condition that affects not only the patient's quality of life, but can also have repercussions on antineoplastic treatment. Therefore, LLI may be a treatment of choice for OM in cancer patients, so far, without presenting any side effects.